Influencing factors for fire performance of simply supported RC beams with implicit and explicit transient creep strain material models. (April 2015) - Lu, Limin; Yuan, Yong; Caspeele, Robby; Taerwe, Luc
Abstract: Knowledge of the temperature dependent material properties of concrete and steel bars is important for understanding the fire-response of a reinforced concrete (RC) structure. At high temperatures, the total strain of concrete is for a large extent influenced by load dependent strains, including transient strain and creep strain, which is also called transient creep strain in literature. The transient creep strain is much larger than the instantaneous stress-related strain under elevated temperature, and can lead to large influences on the deformation of the RC structure. Computer simulations that study the behaviour of heated concrete structures should consider this transient creep strain parameter, otherwise the deformations will be slightly overestimated. This remark is especially necessary for columns, because of their large compression area. However most of the fire resistance simulations use the implicit material models of concrete, as presented by EN 1992-1-2, which is a viable tool in current design practice, but cannot be used whenever transient creep may have an effect on the behaviour of the structural members. So it is necessary to compare the difference of the fire performance of RC beams with implicit and explicit models and study the factors influencing the difference between the two models. To solve this problem, a simplified numerical model proposed by the authors is adopted in this paper, the difference between fire performance of simple supported members with implicit and explicit models are compared and validated by experimental results from previously executed fire tests. Three influencing factors are discussed by comparing the fire behaviour simulation results of RC rectangular beams. The parameters that may have an impact on the difference of fire behaviour of members with the two models studied in this paper are heating curves, reinforcement and the size effect of the cross-section. The conclusions of the parametric study may lead to a better use of material models and more precise simulations on fire behaviour of RC elements, which are required by performance-based fire-resistance design. Highlights: A simplified numerical model for fire behaviour of beams is proposed and validated. Beams simulated with different transient creep strain models(TCSM) are studied. Heating time increases the difference in beams simulated with different TCSM. Reinforcement decrease the difference in beams simulated with different TCSM. Cross-section sizes do not influence the simulation results with different TCSM.